Conductive polypyrrole incorporated nanocellulose/MoS2 film for preparing flexible supercapacitor electrodes - Yuan, Qi; Ma, Ming-Guo (Frontiers of materials science, 2021)
Conductive films have emerged as appealing electrode materials in flexible supercapacitors owing to their conductivity and mechanical flexibility. However, the unsatisfactory electrode structure induced poor output performance and undesirable cycling stability limited their application. Herein, a well-designed film was manufactured by the vacuum filtration and in-situ polymerization method from cellulose nanofibrils (CNFs), molybdenum disulfide (MoS 2 ), and polypyrrole. The electrode presented an outstanding mechanical strength (21.3 MPa) and electrical conductivity (9.70 S·cm −1 ). Meanwhile, the introduce of hydrophilic CNFs induced a desirable increase in diffusion path of electrons and ions, along with the synergistic effect among the three components, further endowed the electrode with excellent specific capacitance (0.734 F·cm −2 ) and good cycling stability (84.50% after 2000 charge/discharge cycles). More importantly, the flexible all-solid-state symmetric supercapacitor delivered a high specific capacitance (1.39 F·cm −2 at 1 mA·cm −2 ) and a volumetric energy density (6.36 mW·h·cm −3 at the power density of 16.35 mW·cm −3 ). This work provided a method for preparing composite films with desired mechanical and electrochemical performance, which can broaden the high-value applications of nanocellulose.